Guest Editors’ Preface - Meyer, Birgit; Hughes, Stephen (Postscripts: The Journal of Sacred Texts, Cultural Histories, and Contemporary Contexts, 2005)
This special issue of Postscripts addresses the interace of religion and film by exploring both hos religion is deployed through film and how film is utilized in service of religion. The issues is based on a workshop, Mediating Religion and Film in a Post-Secular World held June 16-17, 2005, at the University of Amsterdam.